Defect reconstructions in graphene for excellent broadband absorption properties with enhanced bandwidth - Bhattacharyya R.; Kumar Singh V.; Bhattacharyya S.; Maiti P.; Das S. (My University, 2025)
A rapid and controlled reduction method of graphene oxide (GO) along with their performances as broadband frequency absorbers is demonstrated in this report. The microwave-controlled rapid GO reduction technique was adopted to control the exfoliation, structural defects, and the localized electron concentrations while keeping the carbon network in graphene intact. The reduction technique is facile and scalable to produce gram-scale graphene with a controlled manner for preparing a sprayable, lightweight coating (coating thickness ~100–120 μm) throughout a large-area (~225 mm diagonal distances) substrate. The as-prepared coating was explored as active broadband frequency absorbing material in the 4–15 GHz frequency region. We obtained extraordinary absorption properties with an absorptivity average ~96% along with the successive broadening of the bandwidth of ~8.5 GHz throughout the absorption band. The retrieved real and imaginary parts of the surface impedance signify proper impedance matching with the free space; thereby providing high absorption at the aforementioned frequency band. The presence of residual oxygen-containing functional groups results in the differential ability to accumulate electrons, which generate the electric dipole under alternating electromagnetic field while electron hysteresis in these dipoles results in additional surface polarization, which effectively increases the microwave absorption potential of rGO compared to pristine GO. © 2020 Elsevier B.V.